The effect of pyrazinamide and rifampicin on isoniazid metabolism in rats - De Rosa, Helene J.; Baldan, Helen M.; Brunetti, Iguatemy Lourenço [UNESP]; Ximenes, Valdecir Farias [UNESP]; Machado, Rosangela G. P. (Wiley-Blackwell, 2007)
Hepatotoxicity is the main concern during tuberculosis chemotherapy with the first-line drugs isoniazid (INH), rifampicin (RMP) and pyrazinamide (PYR). Since these hepatotoxic events have been associated with INH metabolites, the study aimed to measure the area under curve (AUC) parameter for INH and its metabolites acetylisoniazid (AcINH), hydrazine (Hz) and acetylhydrazine (AcHz), when groups of rats were pre-treated for 21 days with INH alone or in combination with RMP and/or PYR, in the following amounts per kg body weight: INH 100 mg; INH 100 mg + RMP 100 mg; INH 100 mg + PYR 350 mg; INH 100 mg + PYR 350 mg + RMP 100 mg. It was found that co-administration of RMP, PYR and RMP + PYR caused a significant decrease in the AUC for INH. Co-administration of PYR was the only treatment that caused a significant increase in the AUC for Hz and a decrease in the AUC for its acetylated product AcHz. The AUC for AcINH was not significantly altered in any experimental group. In conclusion, the increased metabolism of INH in all the drug combinations and the significantly higher production of Hz in the group INH + PYR might be linked with exacerbated hepatotoxic effects of these drug associations. Copyright (c) 2007 John Wiley & Sons, Ltd.
Keywords: isoniazid; rifampicin; pyrazinamide; acetylisoniazid; acetylhydrazine